Perhitungan Dan Penggunaan Parameter Pertumbuhan Serangga Dalam Penguran Senyawa Penghambat Pertumbuhan Serangga = Quantificatian And Utilisation. Of Insect Growth Parameter n Bioassays Of Insect Growth Inhibitor - Perpustakaan UGM, i-lib ([Yogyakarta] : Program Pascasarjana Universitas Gadjah Mada, 1999)
Studies of the effect of allelochemicals or other insect growth regulator on the development of insect is difficult using parameter currently employed. By measuring the effect growth-inhibiting of seed crude extract of soursop seed, (Annona muricata)